A review of intercultural competence from language teachers' perspective - KARABINAR, SELMA (ELSEVIER SCIENCE BV, 2013)
In foreign language education, the theory of intercultural competence comes to the foreground in the last 20 years. This attributed importance to culture has carried new demands with it for foreign language teachers. It is of importance to determine the place of culture in the curriculum at tertiary level through examining what is taught and what methods and strategies are used in teaching culture in English as a foreign language (EFL) classes. This study examines the how's and why's of culture teaching in English language classes at preparatory schools in Turkey. The study suggests that the integration of culture into language teaching is a must; however, because of time constraints and excessive requirements of syllabi, it does not yet have a distinguished position in foreign language (FL) education at tertiary level in Turkey. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of ALSC 2012
Keywords: Culture; culture teaching; foreign language teaching; intercultural competence; DIMENSION; FINLAND